Origins of the Thick Disk as Traced by the Alpha-Elements of Metal-Poor Giant Stars Selected from RAVE - Ruchti, G; Fulbright, J; Wyse, R; Gilmore, G; Bienaymé, O; Binney, J; Bland-Hawthorn, J; Campbell, R; Freeman, K; Gibson, B; Grebel, E; Helmi, A; et al. (2010)
Theories of thick disk formation can be differentiated by measurements of stellar elemental abundances. We have undertaken a study of metal-poor stars selected from the RAVE spectroscopic survey of bright stars to establish whether or not there is a significant population of metal-poor thick-disk stars ([Fe/H] <~ -1.0) and to measure their elemental abundances. In this paper, we present abundances of four alpha-elements (Mg, Si, Ca, Ti) and iron for a subsample of 212 RGB and 31 RC/HB stars from this study. We find that the [alpha/Fe] ratios are enhanced implying that enrichment proceeded by purely core-collapse supernovae. This requires that star formation in each star forming region had a short duration. The relative lack of scatter in the [alpha/Fe] ratios implies good mixing in the ISM prior to star formation. In addition, the ratios resemble that of the halo, indicating that the halo and thick disk share a similar massive star IMF. We conclude that the alpha enhancement of the metal-poor thick disk implies that direct accretion of stars from dwarf galaxies similar to surviving dwarf galaxies today did not play a major role in the formation of the thick disk.